Management of Craniosynostosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The safety and efficacy of early treatment of craniosynostosis, using minimally invasive endoscopic strip craniectomies, were evaluated prospectively in 100 patients (72 boys, 28 girls) treated at the University of Missouri Hospital, Columbus, MO.